ANALISIS TENTANG KONSOLIDASI TANAH PADA DESA PEMATANG SIMALUNGUN, KECAMATAN SIANTAR, KABUPATEN SIMALUNGUN - MAHYU DANIL (PREMISE LAW JURNAL, 2016)
Land consolidation is a model which is related to the policy in land for public road and facility pupuses and for increasing land efficiency throught land-use management by combining, dividing, changing eliminating, and converting it, followed by the construction of public facilities such as green belt and so on so that the efficient use of land will be obtained as was is stated by nasucha. Landconsolidation, or “LC”, is one of the methods to use land in Indonesia, adopted from Japan and other developed countries where good, appropriated, and  orderly management of limited area of residential land is the basis for the consolidation as an alternative to solve the problems. Keyword :  Land Consolidation, Consolidation Participants